VAGINAL DELIVERY AFTER CESAREAN SECTION - Bashir, Rubina; Khattak, Khurshid (Journal of Ayub Medical College Abbottabad, 2000)
Methods: This retrospective study was conducted in Women & Children Hospital, Abbottabad to determine the outcome of subsequent labour in women with a previous cesarean section for a non-recurrent cause. Results: From 1st January, 1996 to 31st Dec. 1998, 260 patients with a previous lower segment C. Section were admitted out of which 120 patients were selected for trial of labour. 108 (41.53%) patients had a successful vaginal delivery while 12 (4.62%) ended up with a secondary C. Section, indicating a success rate of 90%. Conclusion: This study proves that vaginal delivery is possible in carefully selected patients with lesser maternal morbidity.